2015
DOI: 10.5603/piap.2015.0023
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Bronchopulmonary Aspergillosis Presenting as Lobar or Total Lung Collapse

Abstract: Allergic Bronchopulmonary Aspergillosis presenting as lobar or total lung collapseAlergiczna aspergiloza oskrzelowo-płucna w postaci niedodmy płucThe authors declare no financial disclosure Abstract Introduction: Allergic bronchopulmonary aspergillosis (ABPA) is a T-helper cell 2 (Th2) mediated hypersensitive lung disorder in response to Aspergillus that usually affects asthmatic and cystic fibrosis (CF) patients. ABPA rarely presents as lung collapse and such kind of presentation is very rare in non asthmatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The contraindication of lung trans- plantation is discussed for patients with a Scedosporium-colonized lower respiratory tract, as it was reported in cases of disseminated scedosporiosis (52,53). The role of fungi in exacerbations of chronic bronchitis, lung infections, and as allergic agents in the respiratory tract of cystic fibrosis patients was highlighted recently (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…The contraindication of lung trans- plantation is discussed for patients with a Scedosporium-colonized lower respiratory tract, as it was reported in cases of disseminated scedosporiosis (52,53). The role of fungi in exacerbations of chronic bronchitis, lung infections, and as allergic agents in the respiratory tract of cystic fibrosis patients was highlighted recently (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of ABPA is confirmed when the case presentation meets the criteria established in 2013 by the ABPA Working Group of the International Society for Human and Animal Mycology. If total IgE level are over 1000 IU/mL, two among three criteria are sufficient for establishing the diagnosis of ABPA: positive serum precipitins/Aspergillus fumigatus IgG, eosinophil count >500 cell/L, chest CT consistent with ABPA (mucus impaction, tree-in-bud pattern, centrilobular nodules, mosaic attenuation (31); high attenuation mucus, pathognomonic for ABPA (9,32); segmental, lobar and total lung collapse due to mucus plugs (33)(34)(35); central or peripheral bronchiectasis). Patients with a total IgE levels under 1000 IU/mL, who, otherwise, meet all the remaining criteria are also diagnosed with ABPA (9).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, omalizumab has also proven its efficacy in ABPA, compared to long-term glucocorticoids and it can be administered even in cases with high level of IgE (42). In the case of acute lung collapse, broncho-alveolar lavage during rigid or flexible bronchoscopy helps the lung re-expansion and significant improvement of ABPA symptoms (33,43). For patients with thick sputum, chest physiotherapy and nebulized hypertonic saline solution improve the symptoms (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Cough, fever and hemoptysis are the presenting complaints in both entities. According to a study, almost 31% of patients with ABPA had hemoptysis as primary complaint; [ 5 ]. Similarly, a study on TB revealed that hemoptysis was a symptom in about 79.2% of patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%